Perkembangan Teknologi Digital dan Tantangan Bagi Hukum Administrasi Negara - Efendi, Tifani; Frinaldi, Aldri; Roberia, Roberia (Polyscopia, 2024)
This study explores the impact of digital technology advancements on administrative law, with a focus on the backdrop of globalization and digital transformation across sectors. The research question addressed is the extent to which administrative law can respond to the challenges posed by digital technology in the realms of regulation, data protection, transparency, and government accountability. The research methodology entails literature analysis and case studies to comprehend relevant legal implications. Findings reflect the complexity of administrative law's adaptation to technological advancements, highlighting the need for flexible and responsive regulatory frameworks. Additionally, the study identifies specific areas where existing regulations fall short and proposes adjustments to better align with the dynamic nature of digital innovation. The conclusion emphasizes the necessity for interdisciplinary and interagency collaboration to tackle these challenges, as well as the importance of considering ethical and human rights aspects in policy development. This research contributes to a deeper understanding of the legal transformations required to ensure that administrative law remains effective in the digital age.